1997
DOI: 10.1074/jbc.272.49.31079
|View full text |Cite
|
Sign up to set email alerts
|

CUG Repeats Present in Myotonin Kinase RNA Form Metastable “Slippery” Hairpins

Abstract: We show that CUG repeats form "slippery" hairpins in their natural sequence context of the myotonin kinase gene transcript. This novel type of RNA structure is characterized by strong S 1 and T 1 nuclease and lead cleavages in the terminal loop and by mild lead cleavages in the hairpin stem. The latter effect indicates a relaxed metastable structure of the stem. (CUG) 5 repeats do not form any detectable secondary structure, whereas hairpins of increasing stability are formed by (CUG) 11 , (CUG) 21 , and (CUG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 37 publications
10
147
0
Order By: Relevance
“…The purified and labeled oligonucleotides (4 -5 ϫ 10 5 cpm/reaction) in 10 mM Tris, 40 mM NaCl, and 10 mM MgCl 2 were denatured by heating at 80°C for 5 min followed by renaturation by gradually decreasing the temperature (2°C/min) to the indicated reaction temperature (61). The chemical and enzymatic probes were then added along with the carrier DNA (salmon sperm DNA, 1 g/ l) (Invitrogen).…”
Section: Substrate Preparation For Chemical Modification and Enzymaticmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified and labeled oligonucleotides (4 -5 ϫ 10 5 cpm/reaction) in 10 mM Tris, 40 mM NaCl, and 10 mM MgCl 2 were denatured by heating at 80°C for 5 min followed by renaturation by gradually decreasing the temperature (2°C/min) to the indicated reaction temperature (61). The chemical and enzymatic probes were then added along with the carrier DNA (salmon sperm DNA, 1 g/ l) (Invitrogen).…”
Section: Substrate Preparation For Chemical Modification and Enzymaticmentioning
confidence: 99%
“…5 and 6. The reactions were stopped by addition of a urea-EDTA dye solution (61) followed by quick freezing on dry ice.…”
Section: Substrate Preparation For Chemical Modification and Enzymaticmentioning
confidence: 99%
“…Transcripts containing the uninterrupted double-stranded CAG repeats were shown earlier to activate the RNA-dependent protein kinase PKR (46,47), and form a complex with the specific 63 kDa CAG repeatbinding protein (48). Such interactions resulting in protein activation or sequestration were considered as effects potentially triggering the mechanism of RNA-mediated pathogenesis also in a group of neurodegenerative diseases caused by the CAG repeat expansions (17)(18)(19)(20)(21)49). The prominent role of RNA is well documented for myoblast pathogenesis in two forms of myotonic dystrophy (15), and RNA toxicity is becoming recognized as an underlying cause of the more recently described FXTAS (16 -18).…”
Section: Structures Of the Sca1 Transcripts Are The Same In Cellularmentioning
confidence: 99%
“…The characteristic feature of hairpins formed by the CNG repeats is that their structure rigidity increases with repeat length. For example, hairpin formed by the (CUG)49 has a stem structure which shows a melting temperature much higher than that of (CUG)21 and is completely resistant to the single strand specific probes [33]. Moreover, the long CUG and CAG hairpins behave as regular double-stranded RNA structures with typical RNA-A geometry [34].…”
Section: Cng Repeats Form Hairpin Structures In Transcriptsmentioning
confidence: 99%
“…We have shown that such repeats form stable hairpins, thus the sequestered proteins must be the dsCUG repeat binding proteins [33]. Such proteins were then isolated [45] and shown to co-localize with the expanded transcripts in nuclear foci [46][47][48].…”
Section: Mechanism Of Pathogenesis In Triplet Repeat Expansion Diseasesmentioning
confidence: 99%